Мартирос Сарьян в творчестве Христофора Кушнарева - Телемаковна Хачатрян, Наира (Musical Armenia, 2010)
Letters: pianist, Professor of Yerevan State Conservatory Naira Telemak Khachatryan’s Article “Martiros Saryan in Christapor Kushnarev’s performing art” Their nativity of souls, creative approaches are covered in several letters, which provided wholeheartedly by granddaughters. Kushnaryan’s: Nina Pavlovna and Saryan’s: Ruzan Saryan the director of House Museum. The author also submits C. Kushnaryan’s life and creative path parallels with M. Saryan.